Fe deficiency differentially affects the vacuolar proton pumps in cucumber and soybean roots - Dell'Orto, Marta; De Nisi, Patrizia; Vigani, Gianpiero; Zocchi, Graziano (Frontiers in Plant Science, 2013)
Iron uptake in dicots depends on their ability to induce a set of responses in root cells including rhizosphere acidification through H+ extrusion and apoplastic Fe(III) reduction by FC-R. These responses must be sustained by metabolic rearrangements aimed at providing the required NAD(P)H, ATP and H+. Previous results in Fe-deficient cucumber roots showed that high H+ extrusion is accompanied by increased PEPC activity, involved in the cytosol pH-stat; moreover 31P-NMR analysis revealed increased vacuolar pH and decreased vacuolar [Pi]. The opposite was found in soybean: low rhizosphere acidification, decreased PEPC activity, vacuole acidification and increased vacuolar [Pi]. These findings, highlighting a different impact of the Fe deficiency responses on cytosolic pH in the two species, lead to hypothesize different roles for H+ and Pi movements across the tonoplast in pH homeostasis. The role of vacuole in cytosolic pH-stat involves the V-ATPase and V-PPase activities, which generating the ΔpH and Δψ, mediate the transport of solutes, among which Pi, across the tonoplast. Fluxes of Pi itself in its two ionic forms, H2PO4- predominating in the vacuole and HPO42- in the cytosol, may be involved in pH homeostasis owing to its pH-dependent protonation/deprotonation reactions. Tonoplast enriched fractions were obtained from cucumber and soybean roots grown with or without Fe. Both V-ATPase and V-PPase activities were analyzed and the enrichment and localization of the corresponding proteins in root tissues were determined by Western blot and immunolocalization. V-ATPase did not change its activity and expression level in response to Fe starvation in both species. V-PPase showed a different behavior: in cucumber roots its activity and abundance were decreased, while in Fe-deficient soybean roots they were increased. The distinct role of the two H+ pumps in Pi fluxes between cytoplasm and vacuole in Fe-deficient cucumber and soybean root cells is discussed.